The Mishnaic Sotah Ritual : Temple, Gender and Midrash. - Rosen-Zvi, Ishay (Leiden : BRILL, 2012)
Combining philological, anthropological and cultural tools, this study sheds new light on issues of rabbinic gender economy and sexual morality, and contributes to the nascent scholarship on the formation of the temple in the Mishnah.
The Mishnah and the biblical sotah ritualIII. Interpretation and imitation in the Mishnah; IV. The Roman arena; Chapter Eight Texts and Rituals: The Riddle of Mishnah Sotah; I.A Fantasy of Control--the Mishnah and Rabbinic Discourse of Seduction; II. Textual Rituals; III. One brick on top of another: some conclusions; Afterword: The Temple in the Mishnah; Acknowledgments; Bibliography; Index; Source Index.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 630
Keywords: Mishnah. -- Criticism, interpretation, etc; Adultery (Jewish law); Rabbinical literature -- History and criticism; Women (Jewish law); RELIGION -- Judaism -- Rituals & Practice; Adultery (Jewish law); Rabbinical literature; Women (Jewish law); Electronic books; Criticism, interpretation, etc; Electronic books